Measurement and evaluation on mechanical performances of standing-wave piezoelectric motor of V-shaped sandwich-type transducer having arc tip. (28th February 2022) - Zhang, Yanhu; Jin, Xiandi; Yuan, Xianghui; Zhou, Yang; Zhou, Yuhua; Han, Liling; Li, Jianwei; Ni, Zhijiang; Wang, Xinwei
Highlights: A home-made measured simple system for output performances of linear piezoelectric motors were constructed. A prototype of SWUMs is manufactured and the mechanical characteristics were tested. A basic measurement approach for service performances of linear ultrasonic motors was presented. Static and dynamic performances of linear motor can be measured simultaneously in real time. Abstract: A prototype of the linear standing-wave ultrasonic motors having arc tip is designed and manufactured, and the output performances and mechanical characteristics were tested and evaluated using a home-made measured simple system in this study. Results show that the flexible design of the driving foot is interesting for the performance improvement and simplification design of standing-wave ultrasonic motors. The measured system is simple and is available to evaluate the output performances (thrust and speed) and mechanical characteristics curves of linear motors. The influence trend of preload and driving voltage on output speed is opposite, while the influence trend of thrust is parabola. The peak value of applied voltage is critical for the mechanical characteristic curve of piezoelectric motor. This study also supports a basic measurement approach for service performances of linear ultrasonic motors and the tribological behaviors of motor and/or actuator devices using piezoelectric vibration.